Quality of life following total neoadjuvant therapy for rectal cancer - Wurschi, Georg; Diefenhardt, Markus; Kaufmann, Justus; Ha, Hai Minh; Schneider, Melanie; Schepers von Ohlen, Daphne; Schöneich, Maren; Cieślak, Adrianna; Depardon, Alina; Becker, Jan-Niklas; Rühle, Alexander; Ehret, Felix; et al. (Journal of cancer research and clinical oncology, 2025)
This study aimed to assess the health-related quality of life (HRQoL) in patients with locally advanced rectal cancer (LARC) undergoing total neoadjuvant therapy (TNT), comparing outcomes with the German general population and colorectal cancer (CRC) patients treated with curative intent.
Gesehen am 10.12.2025